THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING SPEAKING OF DESCRIPTIVE TEXT - Alfina Nur Fadila; Tatang Setia; Rajji K. Adireja (Institut Pendidikan Indonesia Garut, 2019)
This study was conducted in order to find out the implementation of Genrebased approach in teaching speaking of descriptive text and the students’ responses toward the implementation of Genre-based approach. This study was conducted at Grade XII Multimedia program of SMK Negeri 4 Garut. This study used descriptive method in non participant observation which researcher did not participate in the activity being observed. The data were obtained through observation and interview. All the data interpreted to answer all research questions. This study revealed that the teacher has understood about the basic principles and stages in Genre-based approach and implementing it properly in his teaching and learning process. Based on the interview with English teacher the researcher found the students showed positive responses toward the implementation of this approach in the class. It can be proven by the improvement of students’ enthusiasm in responding learning and teaching process.